A bibliometric and visualization study of global research trends in sacral Tarlov cyst from 2000 to 2022 - Lu, Yang; Bao, Luyao; Wang, Nan; Chen, Shuang; Qian, Yuzhang; Gu, Jun; Kang, Ran; Xie, Lin (Frontiers in Surgery, 2024)
Background Symptomatic sacral Tarlov cyst (STC) exerts a significant negative impact on the patient's quality of life, highlighting the significance of the increasing number of studies on STC. However, bibliometric analyses in this research field are scarce. Thus, this study aims to provide a comprehensive knowledge structure and identify the research trends of STC through bibliometrics. Methods Articles related to STC from 2000 to 2022 were sourced from the Web of Science Core Collection database. VOSviewer 1.6.16, CiteSpace 6.1.6, GraphPad Prism 8.2.1 and R-package “bibliometrix” were used to analyse the data and generate knowledge maps. Results A total of 930 studies on STC from 2000 to 2022 were included. The findings revealed a consistent yet upward trend in the number of annual publications in this field. The United States, China and Turkey were the most prolific and influential countries contributing to this field, with the University of Illinois, the University of Maryland and the National Institute of Standards & Technology being the most notable research institutions. Key journals include World Neurosurgery [Impact Factor (IF) = 2.210], Journal of Vascular Surgery (IF = 4.860) and Journal of Neurosurgery-Spine (IF = 3.467). Additionally, Tarlov Mj, Tarlov E and Zachariah Mr exhibit the highest number of publications, making them the leading authors in this field. A twenty-year retrospection of research trends using keyword analysis reveals four principal directions, namely “definition”, “pathogenesis”, “diagnosis” and “treatment”. Currently, therapeutic surgical intervention is the key treatment for this disease, with future treatments primarily hinging on minimally invasive methodologies rooted in microendoscopic and endoscopic techniques. Conclusion This pioneering, comprehensive scientific bibliometric study provides a holistic summary of STC research trends and hot spots spanning the past 22 years. The results identify existing research frontiers and chart maps for future studies, serving as a valuable reference for scholars vested in this field.